Evoked Potentials in the Prognosis of Surgical Treatment of Cerebellar Syndrome in Chiari Malformation Type 1 (Global Journal of Medical Research, 2022)
The scientific work presents the results of a neurophysiological examination of 63 patients with cerebellar symptoms in Chiari malformation of type I according to MRI data. All patients underwent a multimodal protocol including BAEP, SSEP and ENMG examination. Neurophysiological criteria of the cerebellar syndrome in type 1 Chiari malformation have been identified, which in a comparative analysis are the most informative in decision making regarding conservative or surgical treatment.
Keywords: chiari malformation type 1; tonsils ectopia; cerebellar syndrome; brainstem auditory evoked potential (BAEP)